IMPLEMENTATION OF AKHLAKUL KARIMAH EDUCATION IN MADRASAH ALIYAH (MULTI CASE STUDY) BASED ON BOARDING SCHOOL AND NONBOARDING SCHOOL STUDIES IN YOGYAKARTA - Jumadi, Jumadi; Mulyadi, Mulyadi; Barizi, Ahmad; Nurul Kawakip, Ahmad; Shodikin, Eko Ngabdul; Mustofa, Amrin; Widiyanto, Widiyanto (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
The demands of life require a balance between faith and piety, reflected in noble morals. Therefore, students need to be prepared and guided to have good morals. Moral education is essential; MA Islamic Center Bin Baz (ICBB) and MA Jamillarohman apply this concept. Research was conducted to evaluate the education system and the implementation of morals in the two schools. This research method uses a qualitative approach and a multi-case study type. Data analysis uses Miles and Huberman's interactive approach and cross-case data analysis. The results of the research show similarities in both schools, such as the goal of forming moral character, the implementation of the education system at the beginning of the school year through meetings with the teacher council, and positive implications for students such as honesty, trustworthiness, devotion to worship, a tendency to help in benevolence, obedience to others. Old, and generous. The difference between the two lies in the karakul Karima pattern at ICBB, which involves Islamic boarding schools, MA Jamillurohman's emphasis on the MAPK curriculum, and MA ICBB's focus on continuing studies in the Middle East and preparing its graduates for work. In contrast, MA Jamillarohman focuses on continuous learning with merit scholarships, memorizing the Koran, and improving studies.